The life and times of T.H. Gallaudet - Sayers, Edna Edith (Lebanon, NH : ForeEdge, an imprint of University of New England, 2018)
Edna Edith Sayers has written the definitive biography of T. H. Gallaudet (1787-1851), celebrated today as the founder of deaf education in America. Sayers traces Gallaudet's work in the fields of deaf education, free common schools, literacy, teacher education and certification, and children's books, while also examining his role in reactionary causes intended to uphold a white, Protestant nation thought to have existed in New England's golden past. Gallaudet's youthful social and political entanglements included involvement with Connecticut's conservative, state-established Congregational Church; the Federalist Party; and the Counter-Enlightenment ideals of Yale, where he was a student. He later embraced anti-immigrant, anti-abolition, and anti-Catholic efforts, and supported the expatriation of free African Americans to settlement on Africa's west coast. As much a history of the paternalistic, bigoted, and class-conscious roots of a reform movement as a story of one man's life, this landmark work will surprise and enlighten both the hearing and Deaf worlds. -- from dust jacket.
Philadelphia to Hartford -- An American theocracy -- Drifting -- Reinventing the wheel -- "What is the gaiety of Paris to me?" -- Mission to the deaf -- Life after deaf I -- Life after deaf II -- Toward a white nation -- The last years.
Includes bibliographical references and index.
Keywords: Gallaudet, T. H. -- 1787-1851.; Gallaudet, T. H. -- 1787-1851.; Teachers of deaf people -- United States -- Biography; Biographies